A Non-Foster Elemental Microstrip Patch Antenna for Cellular Applications - M. Venkata Narayana, Govardhani. Immadi, A. Navya, D. Anirudh, K. Naveen, M. Sriram (International Journal of Advanced Science and Technology, 2020)
In this paper, we proposed an approach to improve the bandwidth of an electrically small antenna which is generally low. In many mobile applications to improve the user experience we can follow this technique. Negative elements in Non-Foster will result in impedance matching thus helps in improving the bandwidth. A microstrip patch antenna is designed to work at 850MHz (for CDMA) using EM model in Advanced Design System (ADS). Its bandwidth is less than 10MHz. There is a significant improvement in bandwidth of 200MHz after embedding the antenna with Non-Foster circuit which are reflected in simulations. Enhancement in performance of antenna which is embedded with Non-Foster circuit is observed when compared with the normal antenna.